Legal NERC with ontologies, Wikipedia and curriculum learning - Cardellino, Cristian; Teruel, Milagro; Alonso Alemany, Laura; Villata, Serena (2024)
Ponencia presentada en la 15th European Chapter of the Association for Computational Linguistics (EACL 2017), 2017, Valencia, Spain. pp.254 - 259, 2017.